IMPLEMENTATION OF THE POLICY PROHIBITING THE USE OF BOTTLED DRINKING WATER - Ni Putu Laksmi Pujayanti; Lilik Antarini; Nyoman Sumawidayani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the implementation of the policy prohibiting the use of bottled drinking water with a capacity of less than 1 liter in Kuta District, Badung Regency. This policy was established through the Circular Letter of the Governor of Bali Number 09 of 2025 as an effort to reduce plastic waste generation. The study used a descriptive qualitative approach with data collection techniques through field observations, in-depth interviews, and documentation studies. Data analysis followed the Miles and Huberman model which includes data collection, data reduction, data presentation, and conclusion drawing. The theory used was the policy implementation model by Van Meter Van Horn (1975). The results of the study indicate that the implementation of the policy has not been running optimally. Although the objectives of the policy have been understood by the implementers and the community, the lack of clear technical guidelines has resulted in non-uniformity in implementation. Limited human resources in the field and a lack of supporting facilities, such as refilling stations, also hamper the policy's effectiveness. Vertical communication between agencies has been implemented through a tiered coordination mechanism, but horizontal communication with businesses and the public has not been evenly distributed. Implementers' attitudes tend to be positive, but this is not accompanied by consistent monitoring and enforcement. Social, economic, and political conditions are relatively supportive, although longstanding community habits remain a challenge. This study concludes that the implementation of the policy banning the use of bottled water with a capacity of less than 1 liter in Kuta Regency is suboptimal. To improve the policy's effectiveness, clear technical guidelines, strengthened ongoing outreach, provision of supporting facilities in public spaces, and improved coordination and oversight between agencies are needed.